Wavelength-Tunable Kerr-Lens Mode-Locked Femtosecond Cr:ZnS Laser With a ∼300-nm Tuning Range From 2.2 to 2.5 μm - Wang, Qing; Wang, Runyu; Yang, Fan; Li, Yan (Frontiers in Physics, 2022)
Tunable 2∼3-μm femtosecond lasers are of high interest in various applications, such as medical diagnostics and molecular spectroscopy. Cr:ZnSe/ZnS is extremely suited for broadband tunable femtosecond lasers due to its excellent emission bands. In this article, we demonstrate a wavelength-tunable Kerr-lens mode-locked Cr:ZnS laser by utilizing a birefringent filter. The group delay dispersion of the operation and the thickness of the birefringent are finely optimized. With the rotation of the birefringent filter, the scheme offers a tuning bandwidth of over 300 nm from 2,220 nm to 2,520 nm. To the best of our knowledge, it is the broadest tuning range among the reported femtosecond Cr:ZnS lasers.